Implementasi Sitamia dalam Pemetaan Budidaya Ikan Air Tawar Berbasis Website di Daerah Lahan Kering TTU - Seran, Krisantus Jumarto Tey; Rema, Yasinta Oktaviana Legu (Jurnal Informatika Universitas Pamulang, 2024)
Fresh water fish pond information spreading over North Central Timor is still very limited to be known by the community. The hardship to obtain the location impacts the fish farmers in doing the transaction with their consumers. This research is conducted with the aim of developing Geographic Information System to the public so that they can easily find the spreading of fish pond locations, particularly around the North Central Timor Regency. The fish pond information system being developed in this research is called SITAMIA. The SITAMIA information system is able to spread information on fish pond, fish products being sold, fish pond location, the distance between buyers and sellers, and the navigation map to the fish selling area. Prototype method is utilized as the roadmap in developing the SITAMIA. The usage of this method is due to its prototype implementation is in line with the users’ need in the community. The development and the application adjustment of this method are based upon the SITAMIA users’ inputs. There are five stages in prototype method namely: Communication, Quick Plan, Modelling Quick Design, Prototype, Deployment Delivery and Feedback. Black box method was employed in website testing where each function of the system was tested. The test result showed that SITAMIA could manage and perform information as expected.